If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -300 + 40 = t Combine like terms: -300 + 40 = -260 -260 = t Solving -260 = t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -260 + -1t = t + -1t Combine like terms: t + -1t = 0 -260 + -1t = 0 Add '260' to each side of the equation. -260 + 260 + -1t = 0 + 260 Combine like terms: -260 + 260 = 0 0 + -1t = 0 + 260 -1t = 0 + 260 Combine like terms: 0 + 260 = 260 -1t = 260 Divide each side by '-1'. t = -260 Simplifying t = -260
| x+1.5x+x+2.5x-8=88 | | 14-2(3p+1)=6(4-2p) | | 0.35x+.05(4-x)=.10(-46) | | 16x+4+23x+2=40 | | 3(z-21)+2(z-2)=13 | | 5x+15+113=4x+8 | | 23x+2+16x+4=40 | | 40x+16x+4=23x+2 | | X^2-9*X+20= | | 3(x+2)-4(3-x)=2x-6 | | n+2-2n=-1 | | c=5b+200forb | | b^2+2b-3= | | 1ox+7=207 | | -4(c-24)=-4c-24 | | 8x+6+7x-3=108 | | -2f+7f=29 | | 2(4x+3)-2=x+20 | | 9x+5=8x-6 | | -27=-7(3b-8) | | 2h-4x=13 | | M+4m=-15 | | 2x^2+x=180 | | E=8b+12nforb | | -23=2n-7n | | 4x-2h=13 | | -18x-24=-9x+3 | | 3(5+7p)=120 | | (6x^3-4)+(2x^3+9)= | | -2(9d-8)=34+6d | | -b-4+3b=3+b | | X+17=3x-23 |